Centrally Administered Cortistation-14 Induces Antidepressant-Like Effects in Mice via Mediating Ghrelin and GABAA Receptor Signaling Pathway - Jiang, JinHong; Peng, YaLi; Liang, XueYa; Li, Shu; Chang, Xin; Li, LongFei; Chang, Min (Frontiers in Pharmacology, 2018)
Cortistatin-14 (CST-14), a recently discovered cyclic neuropeptide, can bind to all five cloned somatostatin receptors (SSTRs) and ghrelin receptor to exert its biological activities and co-exists with GABA within the cortex and hippocampus. However, the role of CST-14 in the control of depression processes is not still clarified. Here, we tested the behavioral effects of CST-14 in the in a variety of classical rodent models of depression (forced swimming test, tail suspension test and novelty-suppressed feeding test). In the models of depression, CST-14 produced antidepressant-like effects, and does not altered locomotor activity levels. And, we found that CST-14 mRNA and BDNF mRNA were significantly decreased in the hippocampus and cortex after mice exposed to stress. Further data show that i.c.v. administration of CST-14 produce rapid antidepressant effects, and does not altered locomotor activity levels. Then these antidepressant-like effects were significantly reversed by [D-Lys3]GHRP-6 (ghrelin receptor antagonist) , but not c-SOM (SSTRs antagonist). Meanwhile, the effects of some neurotransmitter blockers indicates that only GABAA system, but not CRF1 receptor, α/β-adrenergic receptor, is involved in the antidepressant effect of CST-14. The effects of the mTOR inhibitor (rapamycin), the PI3K inhibitor (LY294002) and the p-ERK1/2 inhibitor (U0126) suggesting that the ERK/mTOR or PI3K/Akt/mTOR signaling pathway is not involved in the antidepressant effects of CST-14. Interestingly, intranasal administration of CST-14 led to reducing depressive-like behavior, and near-infrared fluorescent experiments showed the real-time in vivo bio-distribution in brain after intranasal infusion of Cy7.5-CST-14. Taken all together, the results of present study point to a role for CST-14 in the modulation of depression processes via the ghrelin and GABAA receptor, and suggest cortistation may represent a novel strategy for the treatment of depression disorders.